2016
DOI: 10.1111/edth.12171
|View full text |Cite
|
Sign up to set email alerts
|

The MOOC and the Multitude

Abstract: Massive open online courses (MOOCs) take university lectures and other educational materials and make them available for free as online “courses.” Liberal and neoliberal MOOC supporters laud these courses for opening up education to the world while incorporating market dynamics to improve quality and drive down costs. Skeptics claim MOOCs are a bald attempt to privatize higher learning, thus creating an apartheid educational system with traditional universities serving the wealthy while everyone else is left w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The test questions meet the requirements of the test objectives and cover the main knowledge points within the scope of the examination. The quantity and difficulty distribution of the examination content should be consistent with the structure of the teaching content [8].…”
Section: Testsmentioning
confidence: 96%
“…The test questions meet the requirements of the test objectives and cover the main knowledge points within the scope of the examination. The quantity and difficulty distribution of the examination content should be consistent with the structure of the teaching content [8].…”
Section: Testsmentioning
confidence: 96%
“…Many previous studies have shown that web-based multimedia learning modules are more attractive to students and more efficient in terms of both study time and in-class activities, and thereby have a positive effect on student achievement [4,[6][7][8][9]. Furthermore, alongside the backdrop of the Internet, the massive open online course (MOOC) [10,11] and the small private online course (SPOC) [12] models have emerged. Compared with a MOOC, a SPOC is a more suitable teaching method for students in college.…”
Section: Introductionmentioning
confidence: 99%